Modelo de gestión administrativa para la asociación "ASOCOMSANCUM" de la comuna San Antonio de Cumbijín de la ciudad de Salcedo en el año 2020. - Paste Lagua, Nataly Silvana (2020)
The ASOCOMSANCUM association from San Antonio commune in Cumbijin – Salcedo city, is an organization that is regulated by the Superintendency of Popular and Solidary Economy, in charge of collecting milk from the community members who are part of this organization. Also, it has allowed an improvement in the productive development of the large dairy industries, due to the services it offers and the ease of providing them with raw materials. For this reason, the present research project aims to develop the Administrative Management Model that contributes to the organizational development of the association. For this, the parameters of administrative management and organizational development within the association were investigated and analyzed. Through a descriptive study, the existing problems in the organization were evidenced, which in turn made it will possible to obtain a support that validated the proposed solution to the problems of conflicts or delays that impeded development. In addition, for this research, various data collection techniques were carried out, such as interviews and direct observation, which allowed obtaining results on relevant aspects about the organizational development of the association such as: irresponsibility on the part of the partners, inappropriate behavior within the organization, lack of communication and incorrect Administrative Management. Through the results obtained from the data collection, it was evidenced that there was a need to implement an Administrative Management Model with a strategic direction, since it will provide the association with an improvement in organizational development and will also provide a greater degree membership of the partners, in this way each of the guidelines, policies or strategies contained in the Administrative Management Model will be fully complied with.